2013
DOI: 10.1002/2013jb010060
|View full text |Cite
|
Sign up to set email alerts
|

Single‐crystal equation of state of phase D to lower mantle pressures and the effect of hydration on the buoyancy of deep subducted slabs

Abstract: [1] An understanding of the physical properties of the hydrous magnesium silicate phase D is important for the interpretation of the seismic anomalies observed in subducted slabs and to evaluate the effect of hydration on slab dynamics. Here we report the equation of state of phase D (Mg 1.1 Si 1.8 H 2.5 O 6 ) up to 65 GPa obtained from high-precision single-crystal X-ray diffraction. A single-crystal of phase D was loaded in a diamond anvil cell using helium as pressure transmitting medium to ensure quasi-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 78 publications
5
18
1
Order By: Relevance
“…Hushur et al [] observed an 18% increase in K 0 in a high‐pressure X‐ray powder diffraction experiment of FeAl‐free phase D (MgSi 1.7 H 3.0 O 6 ) by fitting the P‐V data in different pressure ranges (0.0001–30 GPa versus 40–55.8 GPa) and proposed the presence of the hydrogen bond symmetrization at 40 GPa. However, this change was not reported in Rosa et al [], as well as in this study. In addition, previous infrared spectroscopy characterization does not support the existence of hydrogen bond symmetrization of FeAl‐free phase D up to 42 GPa at room temperature [ Shieh et al , ].…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Hushur et al [] observed an 18% increase in K 0 in a high‐pressure X‐ray powder diffraction experiment of FeAl‐free phase D (MgSi 1.7 H 3.0 O 6 ) by fitting the P‐V data in different pressure ranges (0.0001–30 GPa versus 40–55.8 GPa) and proposed the presence of the hydrogen bond symmetrization at 40 GPa. However, this change was not reported in Rosa et al [], as well as in this study. In addition, previous infrared spectroscopy characterization does not support the existence of hydrogen bond symmetrization of FeAl‐free phase D up to 42 GPa at room temperature [ Shieh et al , ].…”
Section: Discussioncontrasting
confidence: 80%
“…At lower pressure, the axial compressibility of phase D is found to be anisotropic with the c axis being twice as compressible as the a axis, but at higher pressure, the c / a ratio becomes almost constant or pressure independent (Figure S3b). The critical value of pressure is in the range of 15–40 GPa as found in a series of prior experiments and this study [ Litasov et al , ; Shinmei et al , ; Hushur et al , ; Chang et al , ; Rosa et al , ]. High‐precision data only from single‐crystal XRD clearly show that the c / a ratio becomes constant at 25–30 GPa for FeAl‐free phase D [ Rosa et al , , this study], ~37 GPa for the FeAl‐bearing sample with ∑Fe 3+ /Fe = 0.40 (this study), and ~40 GPa for the FeAl‐bearing sample with ∑Fe 3+ /Fe = 0.94 [ Chang et al , ] (Figure S3b).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Among the DHMS, phase A has a density most similar to phase E and comparably low bulk and shear moduli, K S = 106(1) GPa; G = 61 GPa (Sanchez-Valle et al 2006, 2008. Other DHMS phases such as superhydrous phase B (Rosa et al 2015) and phase D (Rosa et al 2013) have more dense-packed structures and both their elastic moduli and pressure derivatives differ substantially from those of phase E. Therefore, we assume that the shear modulus of phase E shows a similar response to compression as the one of phase A. Consequently, we used the pressure derivative of the shear modulus of iron-bearing phase A, G′ = 1.8 (Sanchez-Valle et al 2008) together with a K 0 ′ of 7.1, consistent with the re-evaluated compression studies of Crichton and Ross (2000) and Shieh et al (2000) on phase E, to compute sound wave velocities of phase E at mantle pressures. We found that at 13 GPa and 300 K, phase E will have compressional and shear wave velocities of 7.33 and 4.88 km/s, respectively, which are about 8% and 16% lower compared to hydrous wadsleyite at the same pressure (Mao et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Anisotropic fabrics of perovskite could serve as a potential explanation of ULM anisotropy but its deformation mechanisms and elastic properties are not sufficiently constrained for a detailed analysis. Recently, experimental studies of the mechanical properties of phase D have shown that LVZ, shear splitting delay times as well as the splitting geometry V SH > V SV observed in the northern part of the Tonga subduction zone at ULM mantle depths could be explained by the presence of 16 vol.% of textured phase D in a hydrous subducted peridotite containing 1.2 wt.% of water (Rosa et al, 2013a(Rosa et al, , 2013b(Rosa et al, , 2012. Interestingly, the sub-slab anisotropy below Taiwan has been ascribed to anisotropic fabrics of hydrous phases (Hu et al, 2012) and particularly, ShyB has been pointed as a candidate to explain sub-slab scatterers below the Tonga slab at TZ depths (Kaneshima, 2013).…”
Section: Introductionmentioning
confidence: 99%